Measuring Women's Empowerment: Gender and Time‐use Agency in Benin, Malawi and Nigeria. Issue 5 (26th July 2022) - Eissler, Sarah; Heckert, Jessica; Myers, Emily; Seymour, Greg; Sinharoy, Sheela; Yount, Kathryn
ABSTRACT: Time use, or how women and men allocate their time, is an important element of empowerment processes. To extend this area of study, this article proposes and explores the concept of time‐use agency, which shifts the focus from the amount of time individuals spend on activities to the strategic choices they make about how to allocate their time. It draws on 92 semi‐structured interviews from three qualitative studies in Benin, Malawi and Nigeria to explore and compare the salience of time‐use agency as a component of empowerment. The article finds that time‐use agency is salient among women and men and dictates how they can make and act upon strategic decisions related to how they allocate their time. It also finds that time‐use agency is tied to other dimensions of agency beyond decision making and ways of exerting influence in the household. Its findings highlight that women's capacity to exercise time‐use agency is conditional on gendered power dynamics and other barriers within households, which together are reciprocally related to local gender norms that dictate how women should spend their time.